Odpowiedzi

2010-03-07T13:10:59+01:00
A) 5*[0,4 - 2/5 : ( -2)] =5*[0,4- (-2/10)]=5*[4/10+2/10]= 5*6/10=30/10=3
b) [0,8 - (1,2 * 5/12 * 0,8)] : (-1/8) =[0,8-(6/5*5/12*4/5)]:(-1/8)= [0,8-(1/2*4/5)]:(-1/8)=[0,8-4/10]:(-1/8)=4/10:(-1/8)=-4/80= -1/20=-0,05
c) - 100 : { - [2 i 3/4 - ( - 0,5) - (-1 i 1/2)]} =-100:{-[11/4+1/2+3/2]}= 100:[-(11/4+2/4+6/4)]=100:(-19/4)=-(100*4/19)=-400/19
2010-03-07T13:16:43+01:00
A) 5*[0,4 - ⅖ : ( -2)] = 5 * [0,4 - ⅖*(-½)] = 5* (⁴/₁₀ + ²/₁₀)= 5 * ⁶/₁₀=³⁰/₁₀=3
b) [0,8 - (1,2 * ⁵/₁₂* 0,8)] : (-⅛) = [0,8 - (¹²/₁₀*⁵/₁₂*⁸/₁₀)] : (-¹/₈) = [⁸/₁₀-(⁶/₅*⁵/₁₂*⁴/₅]:(-⅛) = [⁸/₁₀-(¹²⁰/₃₀₀)]:(-⅛) = [⁴/₅-(²/₅)]:(-⅛) = ²/₅*(-8) = (-¹⁶/₅) = (-3⅕)
c) - 100 : { - [2 ¾ - ( - 0,5) - (-1 ½)]} = -100 : [ - (2,75+0,5+1,5)] = -100:(-4,75) = -¹⁰⁰⁰⁰/₄₇₅ = ⁴⁰⁰/₁₉ = 21¹/₁₉